2016
DOI: 10.1371/journal.pone.0164816
|View full text |Cite|
|
Sign up to set email alerts
|

A Multi-Faceted Approach to Analyse the Effects of Environmental Variables on Geographic Range and Genetic Structure of a Perennial Psammophilous Geophyte: The Case of the Sea Daffodil Pancratium maritimum L. in the Mediterranean Basin

Abstract: The Mediterranean coastline is a dynamic and complex system which owes its complexity to its past and present vicissitudes, e.g. complex tectonic history, climatic fluctuations, and prolonged coexistence with human activities. A plant species that is widespread in this habitat is the sea daffodil, Pancratium maritimum (Amaryllidaceae), which is a perennial clonal geophyte of the coastal sands of the Mediterranean and neighbouring areas, well adapted to the stressful conditions of sand dune environments. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 94 publications
1
20
0
Order By: Relevance
“…They also reported 6 private alleles for populations from Israel and Croatia and 5 private alleles for Rhodes and two different populations from Italy. The numbers of individual analyzed in these populations were different from each other (De Castro et al, 2016). …”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…They also reported 6 private alleles for populations from Israel and Croatia and 5 private alleles for Rhodes and two different populations from Italy. The numbers of individual analyzed in these populations were different from each other (De Castro et al, 2016). …”
Section: Discussionmentioning
confidence: 93%
“…We recommend high priority for these two populations in genetic resource conservation and management studies. De Castro et al (2016) reported 42 private alleles in 17 studied populations, with 1 private allele for the Turkish (Karasu-Sakarya) population. They also reported 6 private alleles for populations from Israel and Croatia and 5 private alleles for Rhodes and two different populations from Italy.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations